Teaching Of The Extrema Of The Function In Mathematical Lessons - Adburaxmanov A.G. (Euro Asian Journal Publishing, 2024)
in this article discusses about teaching of the extrema of the function in mathematical lessons
Keywords: extrema; function; mathematical